The effectiveness of Dietary Approaches to Stop Hypertension (DASH) counselling on estimated 10-year cardiovascular risk among patients with newly diagnosed grade 1 hypertension: A randomised clinical trial. (1st December 2016) - Wong, Martin C.S.; Wang, Harry H.X.; Kwan, Mandy W.M.; Li, Shannon T.S.; Liang, Miaoyin; Fung, Franklin D.H.; Yeung, Ming Sze; Fong, Brian C.Y.; Zhang, De Xing; Chan, David K.L.; Yan, Bryan P.; Coats, Andrew J.S.; et al.
Abstract: Background: The Dietary Approaches to Stop Hypertension (DASH) has been shown to lower blood pressure in the West. However, the real-life impact of DASH on reducing cardiovascular (CV) risk in routine clinical setting has not been studied. Methods: A parallel-group, open-labelled, physician-blinded, randomised controlled trial was conducted in January–June 2013 and followed up for 6- and 12-months in primary care settings in Hong Kong. Patients newly diagnosed with grade 1 hypertension (aged 40–70 years) who had no concomitant medical conditions requiring dietary modifications were consecutively recruited. Subjects were randomised to standard education (usual care) ( n = 275), or usual care plus dietitian-delivered DASH-based dietary counselling in a single one-to-one session (intervention) ( n = 281). Primary outcomes were the changes in estimated 10-year CV risk. Results: Outcome data were available for 504 (90.6%) and 485 (87.2%) patients at 6 and 12 months, respectively. There was no difference in the reduction of 10-year CV risk between the two groups at 6 months (− 0.13%, 95% confidence interval [95% CI] − 0.50% to 0.23%, p = 0.477) and 12 months (− 0.08%, 95% CI − 0.33% to 0.18%, p = 0.568). Multivariate regression analyses showed that male subjects, younger patients, current smokers, subjects with lower educational level, and those who dined out for main meals for ≥ 4 times in a typical week were significantly associated with no improvements in CV risk. Conclusions: The findings may not support automatic referral of newly diagnosed grade 1 hypertensive patients for further one-to-one dietitian counselling on top of primary care physician's usual care. Patients with those risk factors identified should receive more clinical attention to reduce their CV risk. Clinical trial registration: ChiCTR-TRC-13003014 (http://www.chictr.org.cn/enindex.aspx ). Highlights: The one-off dietary counselling by dietitian based on the DASH recipe was tested. The estimated 10-year CV risk decreased significantly in both groups on follow-ups. Automatic dietitian referral for grade 1 hypertensive patients may be unnecessary. Factors associated with no improvements in estimated 10-year CV risk were explored.